Comparison of tethered swimming power and force between national japanese and non-national japanese water polo players - Toyoda, Y.; Toyoda, Y.; Moriyama, S.; Enomoto, I.; Okawa, K.; Suzuki, K.; Akashi, K.; Wakayoshi, K. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Water polo, frequently called "martial arts in water," is an intense game. Recognized as one of the toughest sports (Takagi, 2008), water polo involves two teams, each comprising six field players and one goalkeeper, competing using a ball (Smith, 1998). Field player positions typically consist of a center forward, a center back, and four drivers (Snyder, 2008). While a good throwing ability is essential for the game (Smith, 1998), moving powerfully, overcoming water resistance, and transitioning instantly from stationary to top speed for ball possession also demands swimming strength and power (Wakayoshi, 2018). Power influences swimming speed (Costill et al. , 1983), making it an essential characteristic of the sport. Specifically, the simultaneous movements of eggbeater kick with arm sculling and breaststroke kick with crawl arm stroke are frequently used, combining traction force and speed (Wakayoshi et al. , 2022). Differences in performance levels significantly affect the energy requirements of water polo (Platanou et al. , 2003). Therefore, variations in swimming speed and traction force are crucial. Previous studies have revealed that tetherd force and power differ based on position (Wakayoshi, 2018) and that female players exhibit approximately 70% of the maximum traction force and power as male players (Wakayoshi et al. , 2022). However, no studies have focused on the differences in underwater traction power among water polo players at different competition levels. This study aimed to determine the differences in swimming speed, traction force, and traction power between Japanese elites water polo players and non-elites.